2011
DOI: 10.1038/ng.757
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in lectin complement pathway genes COLEC11 and MASP1 cause 3MC syndrome

Abstract: 3MC syndrome has been proposed as a unifying term to integrate the overlapping Carnevale, Mingarelli, Malpuech and Michels syndromes. These rare autosomal recessive disorders of unknown cause comprise a spectrum of developmental features including characteristic facial dysmorphism, cleft lip and/or palate, craniosynostosis, learning disability, and genital, limb and vesicorenal anomalies. In a cohort of eleven 3MC families, we identified two mutated genes COLEC11 and MASP1 both of which encode proteins within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
264
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(274 citation statements)
references
References 25 publications
6
264
3
1
Order By: Relevance
“…Although MASP-2 is thought to play a key role in activation of the lectin pathway, these data suggested that MASP-1 and/or MASP-3 may be more important than MASP-2 in the phagocytosis and clearance of bacteria. Recently, mutations in the MASP-3 gene have been reported to be a cause of the Carnevale, Mingarelli, Malpuech and Michels syndromes (the so-called 3MC syndrome), a disorder that includes craniofacial defects (27). MASP-3 may also play an important role in embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Although MASP-2 is thought to play a key role in activation of the lectin pathway, these data suggested that MASP-1 and/or MASP-3 may be more important than MASP-2 in the phagocytosis and clearance of bacteria. Recently, mutations in the MASP-3 gene have been reported to be a cause of the Carnevale, Mingarelli, Malpuech and Michels syndromes (the so-called 3MC syndrome), a disorder that includes craniofacial defects (27). MASP-3 may also play an important role in embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant MASP-3 has some activity on insulin-like growth factor-binding protein-5 and some synthetic substrates (27). A critical role of MASP-3 in insulin-like growth factor-binding protein-5 availability during craniofacial, muscle, and neural crest development was suggested based on specific mutations (28)(29)(30). In mice, MASP-1 and MASP-3 play a role in the alternative pathway of complement activation and thus might act as a backup system when the lectin pathway is deficient (31).…”
Section: Lectin Pathway In Critically Ill Childrenmentioning
confidence: 99%
“…However, the exact role is still unclear, because we recently found that a patient deficient in both MASP-1 and MASP-3 retained a functional alternative pathway (9). MASP-3 has an important function during development because its absence causes the so-called 3MC syndrome (16,17). A suggested complement-regulatory role for MAp19 (18) could not be confirmed by us (19), whereas we found that MAp44 competitively inhibited binding of MASP-2 to MBL and, hence, attenuated lectin pathway activity (3).…”
mentioning
confidence: 99%